Pemanfaatan Social Advertising Sebagai Media Promosi Produk Puan Makanan Khas Palembang - Dewi Sartika; Imelda Saluza; Roswaty Roswaty (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2021)
Abstract: The Gulo Puan Business Group, Bangsal village, Pampangan sub-district, Ogan Komering Ilir district, is a producer of products in the form of gulo-puan, sagon-puan and tapel-puan. After the implementation of the PKMS activity, a product innovation in the form of Mrs. Candy was obtained, while in the PKM activity, a product innovation in the form of Mrs. yogurt was obtained. Based on this, partners have been able to compete with similar business actors because they already have a variety of product variants, both in the form of food and beverages. However, this certainly needs to be strengthened again by utilizing technology to introduce products to the wider community. Social advertising is a promotional media that is carried out through social media. This promotional media is considered far more effective, efficient and on target compared to conventional promotional media such as flyers, banners and so on. Partners in PKMS activities have been able to utilize social media as a marketing medium. Therefore, in PKM activities, the implementing team provides training on the use of social advertising as a promotional media for women's products produced by partners. Based on the results of social advertising that has been done 5 times, the results show that as many as 96,212 accounts were successfully reached, of which 98.2% were not followers of accounts with demographics 48.2% male and 51.8% female. As many as 55% of the target to open a profile from Mrs. Candy and from a total of 4,018 accounts that liked ads were obtained.           Keywords: competitive advantage; puan candy; puan yogurt; social advertising;Abstrak: Kelompok Usaha Gulo Puan desa Bangsal kecamatan Pampangan kabupaten Ogan Komering Ilir merupakan penghasil produk berupa gulo puan, sagon puan dan tapel puan. Setelah pelaksanaan kegiatan PKMS diperoleh inovasi produk berupa puan candy, sedangkan pada kegiatan PKM diperoleh inovasi produk berupa puan yogurt. Berdasarkan hal tersebut  mitra telah mampu bersaing dengan pelaku usaha sejenis karena telah memiliki varian produk puan yang beragam, baik berupa makanan maupun minuman. Namun, hal tersebut tentu perlu diperkuat lagi dengan memanfaatkan teknologi guna mengenalkan produk ke Masyarakat luas. Sosial advertising merupakan media promosi yang dilakukan melalui sosial media. Media promosi ini dianggap jauh lebih efektif, efisien dan tepat sasaran dibandingkan dengan media promosi konvensional seperti selebaran, banner dan sebagainya. Mitra pada kegiatan PKMS telah mampu memanfaatkan sosial media sebagai media pemasaran. Oleh karena itu, pada kegiatan PKM tim pelaksana memberikan pelatihan pemanfaatan sosial advertising sebagai  media promosi produk puan yang dihasilkan oleh mitra. Berdasarkan hasil sosial advertising yang telah dilakukan sebanyak 5 kali diperoleh hasil bahwa sebanyak 96.212 akun yang berhasil dijangkau, dimana 98,2%nya bukan pengikut dari akun dengan demografi 48,2% berjenis kelamin laki-laki dan 51,8% perempuan. Sebanyak 55% dari sasaran membuka profil dari puan candy serta dari total keseluruhan diperoleh 4.018 akun yang menyukai iklan.Kata kunci: competitive advantage; puan candy; puan yogurt; social advertising